Robotic Surgery in Otolaryngology and Head and Neck Surgery: A Review - Oliveira, Caio M. (Hindawi Publishing Corporation, 2012)
Recent advancements in robotics technology have allowed more complex surgical procedures to be performed using minimally invasive approaches. In this article, we reviewed the role of robotic assistance in Otolaryngology and Head and Neck Surgery. We highlight the advantages of robot-assisted surgery and its clinical application in this field.